Perancangan Sistem Informasi Administrasi Kepegawaian Pada Kementerian Agama Kabupaten Ogan Ilir - Ridho, Hifzir; Purwani, Fenny; Azmi, M. Kholil (Universitas Multi Data Palembang, 2024)
The Ministry of Religious Affairs Office in Ogan Ilir Regency is experiencing several issues in managing personnel data, such as the difficulty in searching for employee files due to the continued use of manual filing systems. Files are often stored in folders, leading to the frequent loss of employee documents. The storage method proves to be ineffective at the Ministry of Religious Affairs Office in Ogan Ilir Regency, causing difficulties for responsible personnel in locating the required files. This research proposes an Employee Administration Information System at the Ministry of Religious Affairs Office in Ogan Ilir Regency using the Prototype Method to enhance the system's quality and time efficiency. The proposed system aims to be highly effective and easier to implement, as it aligns with the clients' understanding of their needs. The expected outcome is to provide a positive contribution to the administration of personnel data at the Ministry of Religious Affairs Office in Ogan Ilir Regency, ultimately improving the overall organizational performance.